A novel group of pumilio mutations affects the asymmetric division of germline stem cells in the Drosophila ovary. - Lin, H.; Spradling, A.C. (Development, 1997)
Germline stem cells play a pivotal role in gametogenesis; yet little is known about how they are formed, how they divide to self-renew, and how these processes are genetically controlled. Here we describe the self-renewing asymmetric division of germline stem cells in the Drosophila ovarian germline, as marked by the spectrosome, a cytoplasmic structure rich in membrane skeletal proteins. The ontogeny of the spectrosome marks the lineage of germline stem cells. We identified two new groups of mutations in which the divisional asymmetry is disrupted. The first, which we refer to as ovarette (ovt) mutations, was shown to correspond to a novel class of mutations in the pumilio locus. Since pumilio is known to posttranscriptionally repress the expression of target genes at earlier stages of germ cell development, our results suggest that a similar activity is needed to maintain germ line stem cells. We have also identified a second and novel gene, piwi, whose mutations abolish germline stem cell division.